Quality Analysis of Vaberaya.Banyumaskab.Go.Id Website on User Satisfaction on Vaccination Activities in Banyumas District Using Delone and Mclean Success Model - Fitriana, Risa (International Journal of Informatics and Information Systems, 2022)
The development of technology today has become the most important thing in society. This causes the wider information that can be accessed by the public in Indonesia, especially on vaccination activities in the Banyumas area, the people of Banyumas can access the website to carry out vaccination activities. Processes that use technology anywhere and anytime. This study analyzes the quality of the website vaberaya.banyumaskab.go.id using the Delone and McLean Success Model with reference to 6 variables including information quality, system quality, service quality, user satisfaction, usage, and net benefits. This sampling uses questionnaire data with 100 users as respondents who have used the vaberaya.banyumaskab.go.id website. The method in data processing uses a structural equation model or Structure Equation Modeling (SEM), with the help of SmartPLS.